Micromachined piezoresistive tactile sensor array fabricated by bulk-etched MUMPs process - Lomas, Tanom; Tuantranont, Adisorn; Cheevasuvit, Fusak (My University, 2003)
This paper discusses the design, fabrication and testing of a 5×5 micromachined tactile sensor array for the detection of an extremely small force (micrometer-Newton range). Central contacting pads that are trampoline-shape suspended structures and sensor beams are formed using an anisotropic etching of silicon substrate of a MUMPs process chip. A piezoresistive layer of polysilicon embedded in sensor beams is used to detect the displacement of the suspended contacting pad. Each square tactile has dimension of 200 μm × 200 μm with 250 μm center-to-center spacing. The entire sensor area is 1.25 mm × 1.25 mm. The device was characterized under various normal force loads using weight microneedles. The individual sensor element shows the linear response to normal force with good repeatability.